The Agrarian Question in the Views and Activities of Mahatma Gandhi - Joanna Maj (Zeszyty Wiejskie)
The British Empire’s expansive colonial policies consistently pursued in the Indian subcontinent in the late 19th and early 20th centuries led to the shaking of traditional socioeconomic relations. The crisis – caused by sudden demographic growth and extremely difficult climatic conditions – was marked by a disastrous situation in agriculture. Stopping further degradation of the economy required decisive action – especially in the provinces. The creator of the reform program aimed at maximizing the potential of natural and human resources was Mahatma Gandhi – the Father of the Indian Nation, leader of the Indian National Congress, visionary and mystic. Gandhi saw the future of his homeland in the social, moral and economic revival of the countryside. He advocated for a state whose democratic principles would reach out primarily to local communities. Living by example, he aroused hopes among peasants for concrete changes in their lives, lifting themselves out of poverty and overcoming the hopelessness of their social and political predicament.